Symmetry in the front crawl stroke of different skill level of able-bodied and disabled swimmers - Santos, K. B.; Bento, P. C. B.; Payton, C.; Rodacki, A. L. F. (PLOS ONE, 2020)
Although swimming is recognized as a symmetrical sport, equivalence between each body side cannot be insured. Swimmers with physical and motor impairment may present asymmetries that are even more pronounced. Therefore, the objective of this study was to assess the symmetry of temporal coordination in the front crawl stroke phases and their dimensional characteristics among swimmers of different levels of skill and disabled swimmers. Forty-one swimmers (28 men and 13 women, 18,8 ± 3,3 years, divided 21 of them into groups of high and low level of skill and 20 in disabled swimmers group) performed a 50m maximum of front-crawl test while they were recorded by six synchronized cameras (four underwater and two above water) for analysis of the stroke phases, stroke dimensions (anteroposterior, mediolateral and vertical amplitude), index of coordination and hand speed. The symmetry index was calculated by the difference between the right and the left strokes. Comparisons were made using the Kruskal-Wallis test and multivariate comparisons were made using the Mann-Whitney test, with p <0.05. Asymmetry was noted in anteroposterior and mediolateral amplitudes of the stroke, index of coordination, duration of the recovery phase, each of the underwater phases and in the hand speed during the downseep phase, regardless of the level of skill or impairment. The disabled swimmers also showed asymmetry in the vertical amplitude of the stroke as well as in the insweep and upsweep speed. The reasons for these asymmetries may be the preference for unilateral breathing, force imbalance between pairs of homologous muscles and motor control deficit. The training with stereotypic movements may explain the similarity of asymmetries among the different groups of swimmers.